2019
DOI: 10.1007/s10439-019-02308-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Investigation of the IDDSI Flow Test of Liquids Used in Dysphagia Management

Abstract: The International Dysphagia Diet Standardisation Initiative (IDDSI) flow test, using a standard 10-mL syringe, is being adopted in many countries for clinical measurement of the consistency of drinks. The working hypothesis is that thickening drinks to retard flow can be advantageous for individuals who struggle to cope with thin drinks. This study assesses how the IDDSI test relates to rheology and clinical knowledge of physiological flows during swallowing. With no pre-existing analytical solution for intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 39 publications
1
30
0
2
Order By: Relevance
“…The IDDSI flow test was compared to other empirical methods (line-spread test and Bostwick consistometer) as well as rheological methods (viscometer and rheometer) to categorize various liquids. These methods showed that characterization of liquids tested could be similar, but not identical [ 43 , 45 , 46 , 47 , 50 , 55 , 60 ]. Measures of IDDSI flow test may vary depending on the type of thickening agent (starch versus gum) and the liquid used, even though some rheological parameters such as viscosity are similar [ 43 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IDDSI flow test was compared to other empirical methods (line-spread test and Bostwick consistometer) as well as rheological methods (viscometer and rheometer) to categorize various liquids. These methods showed that characterization of liquids tested could be similar, but not identical [ 43 , 45 , 46 , 47 , 50 , 55 , 60 ]. Measures of IDDSI flow test may vary depending on the type of thickening agent (starch versus gum) and the liquid used, even though some rheological parameters such as viscosity are similar [ 43 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…These methods showed that characterization of liquids tested could be similar, but not identical [ 43 , 45 , 46 , 47 , 50 , 55 , 60 ]. Measures of IDDSI flow test may vary depending on the type of thickening agent (starch versus gum) and the liquid used, even though some rheological parameters such as viscosity are similar [ 43 , 45 , 47 ]. Thus, two liquids of the same level IDDSI may have different viscosities or different flows when measured with another method [ 43 , 45 , 46 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…(Sukkar et al., 2018) Actually, a recent study sought to overcome this challenge. (Hanson, Jamshidi, Redfearn, Begley, & Steele, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This test classifies consistency based on the volume of the residual liquid in the syringe after a period of a 10 s flow. The resulting levels are then defined as level 0 thin (0–1 mL liquid remaining), level 1 slightly-thick (1–4 mL), level 2 mildly thick (4–8 mL) and level 3, moderately thick (8–10 mL) [ 48 ]. The new International Dysphagia Diet Standardization Initiative (IDDSI) classification system considers practical measurements for liquids that could be used in kitchens, bedsides and in laboratories.…”
Section: Methods To Assess Texture In the Food Industrymentioning
confidence: 99%